Effect of dietary carbohydrate sources on apparent nutrient digestibility of olive flounder (Paralichthys olivaceus) feed. Issue 1 (December 2016) - Rahman, Md; Lee, Kyeong-Jun; Lee, Sang-Min
Abstract Apparent digestibility coefficients (ADCs) of dry matter, crude protein, crude lipid, nitrogen-free extract, and energy in selected carbohydrate sources including wheat flour (WF), α-potato starch (PS), α-corn starch (CS), Na alginate (AL), dextrin (DEX), and carboxymethyl cellulose (CMC) were determined for olive flounder. The olive flounder averaging 150 ± 8.0 g were held in 300-L tanks at a density of 30 fish per tank. Chromic oxide was used as the inert marker. Feces were collected from the flounder by a fecal collector attached to a fish rearing tank. Apparent dry matter and energy digestibilities of flounder fed WF, PS, CS, and DEX diets were significantly higher than those of fish fed AL and CMC diets. Apparent crude protein digestibility coefficients of flounder fed PS and CS diets were significantly higher than those of fish fed AL, DEX, and CMC diets. Apparent crude lipid and nitrogen-free extract digestibility coefficients of flounder fed PS and DEX diets were significantly higher than those of fish fed WF, CS, AL, and CMC diets. The present findings indicate that PS and DEX could be effectively used as dietary carbohydrate energy compared to WF, CS, AL, and CMC for olive flounder.